THE EFFECT OF PROFESSIONALISM ON EMPLOYEE PERFORMANCE WITH WORK PROCEDURES AS AN INTERVENING VARIABLE AT THE BINJAI CIVIL REGISTRY OFFICE - Wahyudi Hasibuan; Muhammad Isa Indrawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The achievement of organizational goals is only possible because of the efforts of the individuals in the organization, in other words individual performance is related in line with organizational performance in government organizations, if the resources of the government apparatus are good, then the performance of government or bureaucratic institutions will be good too. The performance of government apparatus resources will be good if they have high skills and competencies. This study aims to see the effect of professionalism on employee performance with work procedures as an intervening variable, this type of research is associative quantitative and this research was conducted at the Binjai Civil Registry Service, Jl. Jambi no 3 Binjai. The population of this study was 50 employees and technical the sample used is a saturated sample. This research model uses path analysis, and the measurement tool uses Smart PLS 3.3.3. The results of this study are as follows: Professionalism has a not significant positive effect on employee performance with an original sample value of 0.135 and a P value of 0.067. Professionalism has a positive and significant effect on work procedures with an original sample value of 0.591 and a P value of 0.000. Work procedures have a positive and significant effect on employee performance with an original sample value of 0.799 and a P value of 0.000. Professionalism has a positive and significant effect on Employee Performance through Work Procedures with an original sample value of 0.472 and P values of 0.000.